Analysis of effect of antidepressant drug venlafaxine on length of QT interval in patients with depressive disorder and alcohol dependence - Sanja Vukadinović-Stojanović; Zlatan Stojanović (Биомедицинска истраживања, 2019)
Introduction: Depressive disorder is common in patients with the diagnosis of alcoholism. Comorbidity of depression and alcoholism significantly worsens the clinical status of patients and represents a major therapeutic challenge. The aim of the study was to investigate the effect of the antidepressant drug venlafaxine on the length of QT interval in patients with depressive disorder and alcohol dependence. Methods: The research included 49 male patients (>18 years of age) with alcohol dependence, who were also diagnosed with depressive disorder by using DSM-IV criterion and positive Hamilton Rating Scale for Depression (HRSD) at the very beginning of hospitalization. The patients had been given 37.5 mg of the antidepressant drug venlafaxine twice a day for twenty days. The global QTc interval (12 leads) was determined automatically using ECG device Schiller Cardiovit AT-1, which used "SCHILLER ECG Measurement and Interpretation Software for Children and Adult ECGs". Statistical data processing was performed using SPSS 16.0 programme package for Windows. Results: There was a statistically significant positive association between HRSD score (depression intensity) and the serum levels of creatine kinase isoenzyme MB, i.e. the degree of myocardial damage (p = 0.048). A statistically significant positive correlation between serum gamma-glutamyltransferase levels and the length of QTc interval (p < 0.001) was also found. There was no statistically significant difference in the length of QTc interval before and after venlafaxine administration (p = 0.827), and the average prolongation of the QTc interval was 0.776 ms (95% CI = -6.323 ms-7.874 ms). Conclusion: In our study, we did not prove the negative effect of antidepressant drug venlafaxine on QT interval in patients with depressive disorder and alcohol dependence. In patients with alcohol dependence, the therapy for depression must have a priority due to the proven negative association between depression and the degree of myocardial damage.
Keywords: alcohol dependence; depression; comorbidity; QT interval; venlafaxine